Peningkatan Kreativitas Melukis melalui Media Cotton Bud pada Anak Kelompok B Tk Pertiwi Karangasem - Aminah, Siti (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Developing children's creativity, especially painting creativity, children can express their imagination and can also learn to control their hands, coordinate their thoughts, eyes, and hands, and express themselves through art. Children can be as creative as they wish in arranging colors when painting. Based on this background, this research problem can be formulated, namely: